The Case for RAMC loud. - OUSTERHOUT, JOHN; AGRAWAL, PARAG; ERICKSON, DAVID; KOZYRAKIS, CHRISTOS; LEVERICH, JACOB; MAZIÈRES, DAVID; MITRA, SUBHASISH; NARAYANAN, ARAVIND; ONGARO, DIEGO; GURU6PARULKAR; ROSENBLUM, MENDEL; RUMBLE, STEPHEN M.; et al. (Communications of the ACM, 2011)
The article discusses RAMCloud, a high-performance storage system that stores information in the main memories of hundreds of thousands of servers. RAMCloud presents a solution to the problem of advancements in disk performance failing to keep pace with developments in disk capacity. By storing online data in memory and demoting hard-drive storage to backup or archival duties, RAMCloud offers an alternative to disk-based storage. Benefits of RAMCloud include much higher throughput and much lower storage.